Community-Based Participatory Research: Toward Eliminating Rural Health Disparities - Barbara Ann Graves; Karl Hamner; Nikles Sarah; Haley Wells (Online Journal of Rural Nursing and Health Care, 2015)
Purpose/Aims: Rural communities throughout the US continue to sustain disparities in healthcare access and outcomes despite decades of health research and action. Community-based participatory research (CBPR) has been successful in empowering communities through research and tailored interventions toward the elimination of health disparities. The purpose of this study was to ascertain the community perspective on health issues within a CBPR project framework. Specific goals included identification of county-level key health issues, assessment of health related risk factors, and development of community capacity to deal with significant health challenges while working within a community-university partnership. Methods: A CBPR needs assessment was conducted using multi-method research through key informant interviews, a telephone survey of community residents and a survey of medical professionals to ascertain the community perspective on health issues. Results: Findings showed a wide range of health needs. Epidemiology assessment of county data revealed excess mortality due to cancer, diabetes, heart disease, chronic respiratory disease, accidents, infant mortality and suicide.  Key informant interviews showed the top perceived health-related problems to be lack of insurance coverage, obesity, lack of education, and lack of consistency in primary care. Telephone survey findings revealed the top perceived health problems were poor quality or insufficient health services, lack of insurance, heart disease, cost of care/poverty, cancer, drug abuse, diabetes, lack of senior care, obesity, and pediatric/prenatal care. Implications: This study provides a specific application of CBPR to help reduce rural health disparities.  Data was used to develop a Childhood Obesity Task Force Summit to combat the local obesity epidemic. A Healthy Week Initiative was also implemented. This research can serve as a model for future research and community engagement scholarship as it relates to CBPR as a paradigm to identify, address and eliminate health disparities.